Cancer of the sigmoid colon in an incarcerated right scrotal hernia - Godlewski, Janusz; Tenderenda, Michał; Biernacki, Maciej (Contemporary Oncology/Współczesna Onkologia, 2010)
The case of a 76-year-old man with symptoms of bleeding from the lower part of the alimentary tract and tumour closing the lumen of the colon diagnosed in the colonoscopic examination is presented. An incarcerated loop of sigmoid colon with annular constricting tumour in the right scrotal hernia which the patient had had for a period of many years was detected during the operation. Partial resection of the sigmoid colon with tumour through the right inguinal approach and colon reconstruction by end-to-end anastomosis in the abdominal cavity during laparotomy was performed followed by hernioplasty according to Halsted. There was no complication during the postoperative period. Analysis of the literature has shown the rare possibility of such a course of colon cancer. The casuistic publications, known so far, presented the possibility of incarcerated inguinal or scrotal left side hernia with strangulated colon and incidental presence of cancer. Necrosis and perforation of the colonic wall were also described in some of these records. This paper describes the first case in the available literature initially operated on because of colon cancer symptoms and following intraoperative diagnosis of a tumour in an incarcerated colon loop inside the right scrotal hernia sac. Diagnostic problems, surgical technique and a review of the literature are presented.